Identifikasi Kesiapan Memasuki Dunia Kerja Melalui Profil Soft Skill Siswa SMK - Fitria Rahmi; Liliyana Sari; Suli Sri Rejeki (Puslitbang Sekawan Institute Nusa Tenggara, 2021)
Vocational High School (SMK) is a work-oriented education where graduates are directed to be ready to work and have competitive and comparative advantages. However, the facts on the ground show that vocational students are not optimal in mastering soft skill competencies, so they are not fully ready to enter the world of work due to the lack of relevance of understanding about soft skills between the industrial world and the world of education needed by the world of work. Based on the urgency of the need for soft skills in the world of work, Kantrowitz developed a soft skill measurement instrument, namely Soft skills Performance Measurement (SSPM) using seven soft skill components, but the team modified it according to the characteristics of vocational students into six components including: (1) interpersonal skills , (2) organizational/leadership skills, (3) performance management skills, (4) cultural/political skills, (5) communication/persuasive skills, and (6) self-management skills. The method of implementing this community service activity follows the approach of Vincent II, J. W by modifying the stages of the activity starting from team formation, formulation of goals, identification of stakeholders, needs analysis, priority determination of problem solutions, preparation, implementation, mentoring, review and evaluation. The results of the activity showed that students had soft skill profiles that were at a fairly good level of achievement. The achievement of students' soft skills is a supporting factor in entering the world of work apart from their hard skills.